To solve the quadratic equation \( 4x^2 + 52x + 169 = 0 \) by factoring, we first look for a way to express it as a perfect square trinomial.
-
Observe the coefficients:
- The leading coefficient is \( 4 \), which is \( (2)^2 \).
- The constant term is \( 169 \), which is \( (13)^2 \).
- The middle term \( 52x \) can be represented as \( 2 \cdot 2 \cdot 13 \cdot x \).
-
Rewrite the equation: Since \( 52 = 2 \times 2 \times 13 \), we can write: \[ 4x^2 + 52x + 169 = (2x + 13)^2 \]
-
Set the equation to zero: \[ (2x + 13)^2 = 0 \]
-
Take the square root of both sides: \[ 2x + 13 = 0 \]
-
Solve for \( x \): \[ 2x = -13 \] \[ x = -\frac{13}{2} = -6.5 \]
Thus, the solution to the equation \( 4x^2 + 52x + 169 = 0 \) is: \[ \boxed{-6.5} \]